Answer :

(i) (2x + y) (2x + y)


2x (2x + y) + y (2x + y)


= 4x2 + 2xy + 2xy + 3y


= 4x2 + 4xy + 3y


(ii) (a + 2b) (a – 2b)


a (a – 2b) + 2b (a – 2b)


= a2 – 2ab + 2ab – 4b2


= a2 – 4b2


(iii)


a2 (a2 – bc) + bc (a2 – bc)


= a4 – a2bc + bca2 – b2c2


= a4 – b2c2


(iv)


( + ) - ( + )


= x2 + yx -


= x2 - y2


(v)


2x (2x - ) + (2x - )


= 4x2 - + -


= 4x2


(vi)


2a3 (2a3 – b3) + b3 (2a3 – b3)


= 4a6 – 2a3b3 + 2a3b3 – b6


= 4a6 – b6


(vii)


x4 (x4 - ) + (x4 - )


= x8 – 2x2 + 2x2 -


= (x8 - )


(viii)


x3 (x3 - ) + (x3 - )


= x6 – 1 + 1 -


= x6 -


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

What must be addeRD Sharma - Mathematics

Fill in the blankNCERT - Mathematics Exemplar

Show that:
</p
RD Sharma - Mathematics